Comparative Analysis of Mikrotik Site Filter Using Address List Techniques, Layer7 Protocols, Web Proxy, Mangle and DNS Static - Hidayat, Arif; ., . (International Journal of Engineering and Technology, 2018)
Filtering techniques on Mikrotik routers can be done in various ways. Whether or not a technique in filtering can be seen from passing or not a package that has been defined. Development of filtering techniques in a router more and more, in line with the rapid development of hardware development. The researchers conducted an analysis comparison site on the proxy filter using that technique 5 Address List, Layer7 Protocols, Web Proxy, Mangle and Static DNS. The experiment was done by blocking youtube.com site and facebook.com and implemented on router Mikrotik RB750. From the experiment 5, the filtering technique shows the results of success, with different filtering output behaviors as well as the different block flow mechanisms of each filtering technique.Â Â